Soluble transferrin receptor as an indicator of iron deficiency and febrile seizures - Salma Salma; Rita Arifin; Erial Bahar; Rini Purnamasari (Paediatrica Indonesiana, 2015)
Background Iron deficiency (ID) has a high incidence inIndonesia, and is a risk factor for febrile seizures. The most suitableassay to detect iron deficiency in the presence of inflammationhas not yet been defined. An indicator of ID unaffected byinflammation is needed, soluble transferrin receptor (sTfR) maybe such an indicator.Objective To evaluate ID as a risk factor for febrile seizures inchildren with inflammation by sTfR measurements.Method We conducted an age-matched, case-control study,focused on children experiencing on acute illnesses at the time.Subjects were 80 children matched by age (40 in the case groupwith febrile seizures, and 40 in the control group who were febrilewithout seizures) aged 3 months to 5 years in Mohammad HoesinHospital, Palembang from February to August 2013. Subjects’clinical data and sTfR levels were recorded. Risk factors wereanalyzed with odd ratios and 95% confident intervals. ThesTfR level cut-off point as a predictor of febrile seizures was alsodefined. Other risk factors were analyzed with multivariate logisticregression test.Results Mean sTfR levels were 41.36 (SD 2.04) nmol/L in thecase group and 33.09 (SD 1.02) nmol/L in the control group.Multivariate analysis revealed ID and iron deficient anemia(IDA), as measured by sTfR levels, to be risk factors for febrileseizures (adjusted OR=3.9; 95%CI 1.41 to 10.8; P=0.007 andOR 3.27; 95%CI 1.21 to 8.84; P=0.017, respectively). The sTfRlevel cut-off point that could be used as a predictor of febrileseizures was 37nmol/L.Conclusion Iron deficiency as measured by increased sTfR isa risk factor for febrile seizures in children.